تحسين نسبة الإشارة إلى الضجيج في أنظمة الاتصالات ذات تجميع التقسيم الترددي البصري - مخول مخائيل سليم (Latakia University Journal -Engineering Sciences Series, 2019)
تتضمن مقالتنا تحليل التأثيرات الحرارية على أداء نُظم الاتصالات ذات تجميع التقسيم الترددي (OFDM) البصرية التقليدية، و تقدم تعريفاً و مخططاً صندوقياً لنظام اتصال OFDM مُقترح جديد. من خلال دراستنا الرياضية، التحليلية و الحسابية، وجدنا أن: النظام FM/IM OFDM المُقترح الجديد أكثر حساسية بالإشارة المُستقبلة من مُستقبلات النظام التقليدي OFDM. عند عمل كلا النظامين FM/IM OFDM المُقترح الجديد و التقليدي عند ذات العوامل، كانت عموماً نسبة استطاعة الإشارة المُفيدة إلى الضجيج في النظام FM/IM OFDM المُقترح الجديد أفضل مما كانت علية في النظام التقليدي FM/IM OFDM. النظام FM/IM OFDM المُقترح الجديد قليل التأثر بالضجيج الحراري، و يعمل بأداء جيد عند درجات حرارة عالية مُقارنة بنظام الكشف التقليدي FM/IM OFDM. Our paper contains analysis of the temperatures effects on the performance of the Traditional FM/IM OFDM Communication System, and offers a new definition of the block diagram to the new suggested FM/IM OFDM system. From mathematical analysis, and computation of the new and Traditional techniques, we found: 1. The new suggested System potentially offers improved receiver sensitivity more than Traditional Communication techniques. 2. When the new and Traditional FM/IM OFDM Communication techniques work at the same parameters, SNR in The new coherent FM/IM OFDM Communication System is usually better than Traditional Coherent FM/IM OFDM Communication techniques. 3. The new suggested System does not have effects by a thermal noise, and stability works at the high temperatures comparatively with Traditional FM/IM OFDM system.